Learning Strategies at SD Muhammadiyah 2 Sidoarjo During Covid-19 Pandemic - May Maharani; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study was to determine the methods and strategies used by SD Muhammadiyah 2 Sidoarjo’s learning process in the middle of the Covid-19 pandemic. In this research process, we used the data collection techniques by interviewing, documenting, and observing during the research process. This research is intended to examine various aspects including: the methods, innovations, challenges, facilities and the creativity of SD Muhammadiyah 2 Sidoarjo teachers. This research is using the qualitative-descriptive research with a qualitative approach for the method. The data collection technique of this research is through the process of interview, documentation, and observation. The conclusions of this project is we previously obtained at SD Muhammadiyah 2 Sidoarjo, that during the COVID-19 pandemic it did not make the process of learning activities decline, but instead made learning more creative and also more innovative. As a impacted of the Covid-19 pandemic, schools must change their teaching-learning’s methods to be more effective which is by implementing online learning and offline learning.